(untitled) (Studia austriaca, 2019)
Henrik Ibsen’s naturalistic drama Klein Eyolf (1894) was successfully performed at prestigious theatres in London, Berlin and Vienna, a fact which emphasises the establishment of Naturalism in bourgeois high culture. Carl Henop-Hauswirth’s German parody of Ibsen’s play, entitled Klein-Schreyolf (1895), was performed at one of the many popular theatres in the Viennese suburbs only a few weeks after the premiere. This article analyses the social and artistic circumstances leading to the Ibsen parody. It shows the critical exchange of culture between Vienna’s city centre and periphery.